2014
DOI: 10.1681/asn.2013101125
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Inhibits Erythropoietin Production

Abstract: Anemia is a feature of CKD and a complication of renal transplantation, often caused by impaired production of erythropoietin. The kidney is a target organ for human cytomegalovirus (hCMV) in such patients, but it is not known whether hCMV effects erythropoietin production. We found that kidneys from patients with CKD were positive for hCMV protein and that blood levels of hCMV IgG inversely correlated with red blood cell count. In mice, systemic murine cytomegalovirus infection decreased serum erythropoietin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Therefore, loss of EPOR expression in endothelial cells can accelerate loss of THBS1 expression due to KSHV miRNAs. Human CMV, a β-herpesvirus, was shown to reduce erythropoietin levels under hypoxic conditions52. The observation that KSHV can repress EPOR-dependent STAT5 activation is novel and highlights the differences in the mechanisms adopted by related herpesviruses to inhibit the EPO pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, loss of EPOR expression in endothelial cells can accelerate loss of THBS1 expression due to KSHV miRNAs. Human CMV, a β-herpesvirus, was shown to reduce erythropoietin levels under hypoxic conditions52. The observation that KSHV can repress EPOR-dependent STAT5 activation is novel and highlights the differences in the mechanisms adopted by related herpesviruses to inhibit the EPO pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Direct infection of CD34+ progenitor cells by human cytomegalovirus may be involved in the viral-induced myelosuppression [25]. In addition, HCMV infection can inhibit the production of erythropoietin and induce or exacerbate anemia [26]. It has been reported that human cytomegalovirus can sequestrate in human renal and mammary epithelial cells [27] and induce TGF-β1 activation in renal tubular epithelial cells after epithelial-tomesenchymal transition [28].…”
Section: Discussionmentioning
confidence: 99%
“…As CMV antigenemia‐positive patients are often administered preemptive therapy with ganciclovir, it is possible that myelosuppression due to ganciclovir will also affect erythropoiesis in these patients 25,26 . As for another possible reason, CMV also shows an inhibitory effect on BFU‐E in vitro assays and on erythropoietin, indicating that CMV may have a direct inhibitory effect on erythrocyte generation 27–29 . In our previous study on pediatric cord blood transplantation, CMV infection was not observed after upon transfusion of leukoreduced blood components 30 .…”
Section: Discussionmentioning
confidence: 97%